USE OF COMMENTARY GENRE AND SPECIFIC CHARACTERISTICS IN UZBEK SPORTS JOURNALISM - Toshkhujaev Z.A. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
There is a concept that sport is for fans. However, not all sports enthusiasts are well versed in this field. He looks at the ongoing competitions and games with the eyes of an ordinary amateur and spectator. It's no secret that commentary is one of the most widely used genres in sports journalism. This direction is characterized by special complexity. Therefore, there is always a great need for a good commentator in sports journalism. In this article, the peculiarities of commenting on competitions in Uzbek sports journalism, the specialization of commentators, and the use of genres of commentary and reportage are considered.